Effect of Different Concentration of Ri Plasmid on Division of Electrotreated Cell Suspension Culture derived from Stem Callus of Vicia faba L. Plants Embedded in Agar Multiple Drops - Sahla Zedan; Mozahim Al-Malah (College of Education for Pure Sciences, 2021)
Samples of cell suspension represents seven different densities were exposed to three electrotreatment 40, 50, 60 volt and for a period of time 50, 100 msec then the densities were mixed with different concentration of Ri plasmid 25, 50, 75 Microliter. The electrotreatment samples cultured by embedding in to agar drops in solid-liquid cultures. Results proved that the electrotreatment enhanced division of cell suspension and caused a clear increase of microcolonies, the total number of colonies reached 3276 when suspension culture was exposed to 50v / 100 msec., these colonies developed to microcalli and the percentage was 90%. The Callus developed from these colonies was light green in color and friable in texture.